Correction to: Deciphering cleaner and sustainable frontiers in scientific cow waste valorization: a review (Environmental Monitoring and Assessment, (2024), 196, 10, (988), 10.1007/s10661-024-13120-0) - Kushwaha J.; Singh Y.; Yadav S.K.; Sheth P.N.; Mahesh M.S.; Dhoble A.S. (My University, 2025)
The original version of this article unfortunately contained an error in the heading of Table 2. On page 8, the heading of Table 2 continuation should be corrected from "cow urine" to "cow dung". © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.